IMPLEMENTASI PENDEKATAN SUPERVISI KOLABORATIF DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU SMP NEGERI 48 SELUMA - Melati Melati (Manajer Pendididikan, 2022)
The general objective of this research is to describe the implementation of the collaborative supervision approach in improving the professional competence of teachers at SMP Negeri 48 Seluma. Meanwhile, the specific objectives of this research are: 1) To describe the process of collaborative supervision approach carried out by the principal of SMP Negeri 48 Seluma in improving the professional competence of teachers; 2) To describe the obstacles faced by the principal of SMP Negeri 48 Seluma in implementing a collaborative supervision approach to improve the professional competence of teachers; 3) To improve the professional competence of teachers at SMP Negeri 48 Seluma after the collaborative supervision approach was applied. The research method used in this study is the school action research method. Data collection techniques are carried out for data processing which is carried out quantitatively and qualitatively. The analytical technique used is descriptive qualitative analysis. The steps in the data analysis process are: data reduction, data display/presentation, and conclusion drawing/verification. The conclusion of this research in general is that the collaborative supervision approach process carried out by the principal of SMP Negeri 48 Seluma in improving the professional competence of teachers is going quite well. This is proven by the real actions taken by the principal in a systematic and programmed manner.